Cognitive and Neuroplasticity Mechanisms by Which Congenital or Early Blindness May Confer a Protective Effect Against Schizophrenia - Silverstein, Steven; Wang, Yushi; Keane, Brian P. (Frontiers in Psychology, 2013)
Several authors have noted that there are no reported cases of people with schizophrenia who were born blind or who developed blindness shortly after birth, suggesting that congenital or early (C/E) blindness may serve as a protective factor against schizophrenia. By what mechanisms might this effect operate? Here, we hypothesize that C/E blindness offers protection by strengthening cognitive functions whose impairment characterizes schizophrenia, and by constraining cognitive processes that exhibit excessive flexibility in schizophrenia. After briefly summarizing evidence that schizophrenia is fundamentally a cognitive disorder, we review areas of perceptual and cognitive function that are both impaired in the illness and augmented in C/E blindness, as compared to healthy sighted individuals. We next discuss: 1) the role of neuroplasticity in driving these cognitive changes in C/E blindness; 2) evidence that C/E blindness does not confer protective effects against other mental disorders; and 3) evidence that other forms of C/E sensory loss (e.g., deafness) do not reduce the risk of schizophrenia. We conclude by discussing implications of these data for designing cognitive training interventions to reduce schizophrenia-related cognitive impairment, and perhaps to reduce the likelihood of the development of the disorder itself.